2022
DOI: 10.1016/j.pec.2021.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Exploring variables related to medical surrogate decision-making accuracy during the COVID-19 pandemic

Abstract: Objective Surrogate medical decision making is common in the United States healthcare system. Variables that may influence surrogate decision making have been proposed. Little work has examined relations between these variables and outcomes of surrogate decision making. This study investigated whether surrogates’ characteristics, including their knowledge of treatment options, and interpersonal factors predicted surrogates’ accuracy and intervention selections. Specifically, predictor variables in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Though it has been previously established that surrogate decision‐makers often incorrectly predict patient's wishes in various clinical scenarios (Shalowitz et al, 2006 ), there is limited research that captured nurses' perceptions of this issue during the pandemic. Spalding and Edelstein ( 2022 ) found that during the pandemic, uncertainty regarding illness trajectory exacerbated uncertainty about patient wishes amongst surrogate decision‐makers. Since nurses in this study described perceptions that patient wishes were unknown or that surrogates decisions did not reflect patient wishes, it may be important to understand that visitation restrictions and surrogates' motivation to see loved ones are powerful motivators of decision making that may reappear in another pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though it has been previously established that surrogate decision‐makers often incorrectly predict patient's wishes in various clinical scenarios (Shalowitz et al, 2006 ), there is limited research that captured nurses' perceptions of this issue during the pandemic. Spalding and Edelstein ( 2022 ) found that during the pandemic, uncertainty regarding illness trajectory exacerbated uncertainty about patient wishes amongst surrogate decision‐makers. Since nurses in this study described perceptions that patient wishes were unknown or that surrogates decisions did not reflect patient wishes, it may be important to understand that visitation restrictions and surrogates' motivation to see loved ones are powerful motivators of decision making that may reappear in another pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…there is limited research that captured nurses' perceptions of this issue during the pandemic. Spalding and Edelstein (2022) Despite significant barriers to providing quality care, nurses described situations in which they perceived that their personal strengths and values enabled them to provide good care and they verbalized a commitment to treating patients as family members. Goethals et al (2010) described how some expert nurses were able to break away from conformist decision-making and behaviours, combining critical thinking and identification of patient needs to identify a pathway forward.…”
Section: Discussionmentioning
confidence: 99%
“…Participants prioritized the perceived needs and preferences of the residents to the best of their abilities when making their decisions. Unfortunately, emerging literature on surrogate decision-making during the COVID-19 pandemic has shown that surrogates often have poor accuracy in predicting patient preferences [ 50 ]. These discrepancies appear relevant in this study, as some care partners described moving the residents despite their expressed preferences to stay in LTC.…”
Section: Discussionmentioning
confidence: 99%
“…Individual decision-making styles tend to be habitual, and people with different decisionmaking styles react differently in specific decision contexts based on established habits (Scott and Bruce, 1995). Decision-making style is an important factor affecting behavior in many fields, such as career development (Mau, 1995;Tinsley et al, 2002;Paivandy et al, 2008), team effectiveness (Verma et al, 2016), school choice (Ueichi et al, 2012), consumption (Zhu et al, 2012), traffic safety (Ju et al, 2019), medical care (Spalding and Edelstein, 2021), and gambling (Cosenza et al, 2019). At the same time, decision-making style is closely related to personality traits (Byrne et al, 2015;Wise et al, 2015;Iennaco et al, 2018;Farcic et al, 2020).…”
Section: Decision-making Stylesmentioning
confidence: 99%